The battle for Roar - McLachlan, Jenny (McLachlan, Jenny. Land of Roar, 2021)
Rose and Arthur are back in Roar, on a voyage that takes them further than they've ever been before: beyond The End. It's an amazing adventure full of secrets, surprises and fairies with fangs, but then a mysterious storm changes everything. Shipwrecked on a strange island, they make a shocking discovery. Could this be the end of Roar?